TUTURAN IMPERATIF GURU DALAM PEMBELAJARAN DI TAMAN KANAK-KANAK FKIP UNIVERSITAS RIAU - Pina Febrina; Dudung Burhanudin; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study discusses the imperative speech teacher in kindergarten FKIP University of Riau. This study used a qualitative approach and descriptive method that aims to describe the imperative speech teacher. Subject of this research were four teachers who taught in all classes in Preschool Guidance and Counseling, University of Riau is in a kindergarten, kindergarten and kindergarten B1 B2. This research uses verbal data type that originates in the utterances teacher in learning in kindergarten FKIP University of Riau. Data obtained using the technique of recording and record, then classified based on the types of sentences and then formulated into a knot. Based on the analysis of the data it can be concluded that the pragmatic imperative form contained in the speech teacher in learning in kindergarten FKIP Riau University comprises 12 form imperatives, namely: (1) Imperative Command, (2) Prohibition Imperative, (3) Imperative Pressure , (4) Imperative Ngelulu, (5) appeal Imperative, (6) Persilaan Imperative, (7) Imperative Demand, (8) Allow Imperative, (9) Provision Imperative Congratulations, (10) Persuasion Imperative, (11) Imperative Call , and (12) Imperative Ignorance. The imperative utterances spoken kesantunannya teacher based strategy. Strategic imperatives in the utterances teacher uses direct speech to the strategy of positive politeness and negative politeness. Judging is based on structural, imperative sentences directly used by teachers when the communication between teachers and children are considered less polite as narrative conveyed directly and very little use as a marker kesantunannya markers.Key words: the imperative of teachers, learning in kindergarten